PENGURANGAN NH3 DAN H2S MENGGUNAKAN PLAT INTERCEPTOR BERMEDIA MINYAK PELUMAS PADA BERBAGAI VARIASI ALIRAN ASAP - Sihombing, Gabriel Cristian CR; Winaya, I Nyoman Suprapta; Darma, I Wayan Arya (Teknik Desain Mekanika, 2024)
Abstract This study aims to develop an oil-lubricated waste oil interceptor plate to minimize the amount of smoke and odor emitted from a drying system such as a Rotary Dryer (RD). The water vapor smoke emitted from the RD can contain pollutants as odoriferous gases such as ammonia (NH3) and hydrogen sulfide (H2S), which greatly depend on the type of organic waste being dried and the operational conditions of the machine. The interceptor plate is constructed in the form of blocks measuring 1m in length, 0.12m in width, and 0.13m in height, where the plates are arranged in a zigzag pattern to impede the flow of smoke gas so that pollutant particles are trapped and adhere to the waste oil media layered on the surface of the plate. The smoke flow rate is varied from 3 to 6 m/s to observe the effectiveness of capturing pollutant gases during the 120-second testing duration. The investigation results show that the percentage decrease in pollutant gases occurs with each increase in smoke flow rate given, with the lowest at a speed of 6 m/s, namely NH3 from 63.73 to 10.34 ppm and H2S from 6.3 to 1.9 ppm. The effectiveness and efficiency at a speed of 6 m/s are measured as optimal at 53.6% and 84.1% respectively. Keywords: Interceptor plate, smoke and smell, used oil, waste lunricant, effectivity and efficiency.